2010
DOI: 10.1002/art.27649
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depressive symptoms in fibromyalgia are related to poor perception of health but not to pain sensitivity or cerebral processing of pain

Abstract: Objective. Mood disturbance is common among patients with fibromyalgia (FM), but the influence of psychological symptoms on pain processing in this disorder is unknown. We undertook the present study to investigate the differential effect of depressive symptoms, anxiety, and catastrophizing on 1) pain symptoms and subjective ratings of general health status and 2) sensitivity to pain and cerebral processing of pressure pain.Methods. Eighty-three women (mean ؎ SD age 43.8 ؎ 8. Results. A correlation analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
54
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 41 publications
11
54
2
8
Order By: Relevance
“…However, Giesecke et al [6] observed that the level of depression was associated to the magnitude of neuronal activation in brain regions involved in affective-motivational dimensions of pain. These results are in line with the fact that higher levels of depression in FM are related to poorer self-reported FM symptomatology factors, especially those emotion-related such as higher affective distress and lower perception of social support [7], as well as with a lower general health perception [5]. However, the association between depressive symptoms and sleep quality, fatigue, physical function, overall FM severity, and HRQoL needs also to be studied in a large sample of women with FM in order to characterize the potential deleterious influence of mood disorders in women with FM.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, Giesecke et al [6] observed that the level of depression was associated to the magnitude of neuronal activation in brain regions involved in affective-motivational dimensions of pain. These results are in line with the fact that higher levels of depression in FM are related to poorer self-reported FM symptomatology factors, especially those emotion-related such as higher affective distress and lower perception of social support [7], as well as with a lower general health perception [5]. However, the association between depressive symptoms and sleep quality, fatigue, physical function, overall FM severity, and HRQoL needs also to be studied in a large sample of women with FM in order to characterize the potential deleterious influence of mood disorders in women with FM.…”
Section: Introductionsupporting
confidence: 83%
“…Previous studies suggest that depression is not associated either to pain intensity or to brain activity during experimentally induced pain in FM patients [5,6]. However, Giesecke et al [6] observed that the level of depression was associated to the magnitude of neuronal activation in brain regions involved in affective-motivational dimensions of pain.…”
Section: Introductionmentioning
confidence: 97%
“…Symptoms of depression and the presence of MDD were associated with the magnitude of longer lasting pain-evoked neuronal activations in brain regions associated with affective pain processing (the amygdala and contralateral anterior insula) (Giesecke et al 2005). In contrast, a study with 83 subjects showed that depressive symptoms, anxiety and catastrophizing scores were correlated, but did not correlate with ratings of clinical pain, nor with sensitivity to pressure pain (Jensen et al 2010). Brain activity during short-lasting experimental pain was not modulated by depressive symptoms, anxiety, or catastrophizing.…”
Section: Discussionmentioning
confidence: 89%
“…De hecho, en este trabajo, la percepción de autoeficacia ha sido la única variable cognitiva que ha presentado relaciones significativas con la depresión, la discapacidad y la intensidad del dolor. Del mismo modo, las relaciones significativas obtenidas respecto del Catastrofismo, sugieren su importancia en la ansiedad informada por estos pacientes, siendo coherente con los resultados de otros estudios (Arnow et al, 2011;Börsbo, Gerdle y Peolsson, 2010;Gormsen, Rosenberg, Bach y Jensen, 2010;Jensen et al, 2010) y con las formulaciones teóricas acerca del papel de los pensamientos catastrofistas en el incremento de la ansiedad, tanto en el caso de estos pacientes como en el de otros problemas de dolor crónico (Leeuw et al, 2007;Pastor et al, 2011). La ausencia anales de psicología, 2014, vol.…”
Section: Discussionunclassified
“…La ausencia anales de psicología, 2014, vol. 30, nº 1 (enero) de relaciones significativas con la Depresión, apoyaría la interpretación anterior aunque este es un resultado específico de este trabajo pues los autores anteriores encontraron relaciones significativas también con esta variable (Brösbo et al, 2010;Gormsen et al, 2010;Jensen et al, 2010). Así pues, aunque tanto la Autoeficacia como el Catastrofismo se han relacionado con el distrés global en el sentido esperado desde la teoría, cabe destacar la relación diferencial que han establecido con la ansiedad y la depresión.…”
Section: Discussionunclassified